Autonomy and subordination: virtuous work in light of aristotelian practical knowledge in organizational theory - Pinto-Garay, Javier; Scalzo, Germán; Ferrero, Ignacio (My University, 2021)
This paper aims to integrate the concept of autonomous and subordinated work into Aristotelian organizational theory by enhancing the epistemological framework of neo-Aristotelianism and by adding a Thomistic interpretation of organizational practical knowledge. We sustain that, in order to advance our understanding of the firm in terms of excellence and the common good, the concept of practical knowledge applied to organizational theory requires reflection on the nature of work in modern organizations. For this, we will explain (i) how an organization that aims for excellence is most appropriately defined as a community of autonomous work, (ii) how practical knowledge in organizations must be defined considering work as deliberative production and, finally, (iii) how productivity in organizations is best described when work is envisioned in terms of autonomy and subordination. ©2021 Business & Professional Ethics Journal.
Keywords: Common good; Neo-Aristotelianism; Organizational theory; Practical knowledge